2021
DOI: 10.3389/fpsyg.2021.673514
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation During COVID-19 Pandemic. Perceived Stress and Containment Measures Compliance Among Polish and Italian Residents

Abstract: BackgroundIn this study, we analyze the association of social isolation in the first phase of the pandemic with perceived stress among residents of Poland and Italy with a look at how these populations adjust to and comply with implemented regulations, guidelines, and restrictions.Materials and MethodsInternet survey with Perceived Stress Scale (PSS-10) and questions regarding mobility patterns, attitude, and propensity to adjust toward the implemented measures and current health condition was made among Polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
15
1
4
Order By: Relevance
“…Consequently, it is difficult to assess the extent to which the values obtained reflect a gradually deteriorating functioning in or, on the contrary, an increasing adaptation to the epidemic situation. Previously conducted large studies [ 5 ] indicate, however, that the level of stress among Polish male citizens (without distinguishing between sexual orientation) was at a much lower level during the first wave of the pandemic (the average PSS-10 score at that time was 19.66 vs. 24.71 in the present study during the third wave). In addition, research on quality of life in Gdańsk (part of the studied Tri-City agglomeration) conducted in June 2021, already after the end of the third wave, on a group of 1500 people [ 6 ] indicated that nearly half of the respondents (48.1%) assessed their mental well-being as worse than before the pandemic.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Consequently, it is difficult to assess the extent to which the values obtained reflect a gradually deteriorating functioning in or, on the contrary, an increasing adaptation to the epidemic situation. Previously conducted large studies [ 5 ] indicate, however, that the level of stress among Polish male citizens (without distinguishing between sexual orientation) was at a much lower level during the first wave of the pandemic (the average PSS-10 score at that time was 19.66 vs. 24.71 in the present study during the third wave). In addition, research on quality of life in Gdańsk (part of the studied Tri-City agglomeration) conducted in June 2021, already after the end of the third wave, on a group of 1500 people [ 6 ] indicated that nearly half of the respondents (48.1%) assessed their mental well-being as worse than before the pandemic.…”
Section: Discussioncontrasting
confidence: 73%
“…However, although the problem of using single-item scales and single elements of multi-item scales is known [ 56 ], the value of comparability is worth recognizing. During the COVID-19 pandemic, a similar study was conducted on the perceived level of stress among Polish and Italian residents [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants agreed to voluntarily participate in the study by signing an informed consent. They were asked to fill in the survey consisting of two parts: the first part included a respondent's particulars (age, sex, year of study) and ten close-ended questions concerning the symptoms of SSDs and pain (Likert scale) [39][40][41][42][43][44][45]. The second part consisted of standardized psychological questionnaires, PSS10 (perceived stress scale), Mini-Cope (Inventory for measuring coping with stress), DS14 (Type-D scale) [46][47][48][49][50][51][52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…In view of the above we investigated the attitude and perception of health protection measures against COVID-19 during the first pandemic wave in Italy and Poland, to inform public health policy makers on the respective determinants. Despite Italy being more heavily hit than Poland during the first COVID-19 wave, social restrictions in the latter two countries were in fact similar ( Dong et al, 2020 ; Roser et al, 2020 ; Grabowski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%